Connected Histories: A New Web Search Tool for British Historians. - HITCHCOCK, TIM; SHOEMAKER, ROBERT; WINTERS, JANE (History, 2011)
The article discusses the Application Programming Interface (API) Connected Histories, an online resource providing access to materials concerning British history from the sixteenth to the nineteenth centuries. The API allows users to access several online databases and resources, including British History Online, British Museum Prints and Drawings, and the Clergy of the Church of England Database. The author notes that Connected Histories was funded by the e-Content Programme of the Joint Information Systems Committee (JISC) and is located at http://www.connectedhistories.org.